Study on the shear and deformation characteristics of geogrid-reinforced gravelly soils based on large-scale triaxial tests - Liu, Jie; Pan, Jiadong; Wang, Bin; Hu, Changtao; Liu, Qinli (Frontiers in Earth Science, 2024)
Geogrid reinforcement has a limiting effect on the lateral deformation and thus improves the shear strength of the soil, the overall strength of the soil and the overall stability of the corresponding geotechnical structure. In this study, large-scale triaxial tests without and with geogrid reinforcement were conducted on three typical gravelly soils in Xinjiang using a large-scale triaxial apparatus. The shear strength and deformation characteristics of gravelly soils with different particle shapes and the stress-strain relations, strength characteristics, damage patterns, and reinforcement effects of gravelly soils with and without reinforcement were investigated. Geogrid reinforcement effectively enhances the strength of the soil; the internal friction angle remained relatively constant with and without reinforcement, whereas the cohesive force increased significantly. The reinforcement effects interpreted from the results obtained from the triaxial tests were discovered when a certain deformation or relative displacement with the reinforcement materials of the soil occurred. Under uniform test conditions, the volumetric strain of the samples of gravelly soil with reinforcement significantly decreased with increasing confining pressure, and the difference in volumetric strains with and without reinforcement was greater when the confining pressure was higher. The highlight of this study is its significance in explaining the reinforcement mechanism in gravelly soils and in selecting engineering design parameters.